Groundwater overexploitation in the North China Plain: A path to sustainability - Kinzelbach, Wolfgang; Wang, Haijing; Li, Yu; Wang, Lu; Li, Ning (Bern Springer Nature, 2022)
Over-pumping of aquifers is a worldwide problem, mainly caused by agricultural water use. Among its consequences are the falling dry of streams and wetlands, soil subsidence, die-off of phreatophytic vegetation, saline water intrusion, increased pumping cost and loss of storage needed for drought relief. Stopping or reversing the trend requires management interventions. The North China Plain serves as an example. A management system is set up for a typical county. It contains three components: monitoring, decision support based on modelling, and implementation in the field. Besides all monitoring data, the decision support module contains an irrigation calculator, a box model, and a distributed groundwater model to project the outcomes of different water allocation scenarios. In view of grain security, a solution combines an adaptation of the cropping system with imports of surface water from the South. The Open Access book does not only describe the problem and the path to its solution. It also gives access to nine manuals concerning methods used. They include computer programs and the game Save the Water. The Chinese experience should be of considerable interest to other regions in the world which suffer from over-pumping of aquifers.
English
Keywords: Hydrology & the hydrosphere; Sustainability; Environmental monitoring; Analytical chemistry; Agricultural science; Groundwater management; Groundwater depletion; Groundwater modelling; Monitoring of groundwater levels; Pumping tests for monitoring of pumping rates of wells; Subsidized land fallowing; Groundwater game app; Smart metering of pumping wells; Smart metering of electricity consumption; Surface water diversion; Decision support system; Open Access